Islamic Educational Institutions in the VUCA Era: Quality Challenges and Adaptive Responses - Adam Damiri; Aimah, Siti (Ahlussunnah: Journal of Islamic Education, 2026)
This study aims to analyze quality challenges and formulate adaptive responses of Islamic educational institutions in the VUCA era, characterized by volatility, uncertainty, complexity, and ambiguity. This research employs a qualitative approach with a case study design in an Islamic educational institution. Data were collected through interviews, observations, and document analysis, and analyzed using an interactive model. The findings reveal that the main challenges include the dichotomy between religious and general knowledge, limited critical digital literacy, inadequate human resource readiness, and ambiguous quality standards. Adaptive responses are manifested through integrative curriculum transformation, adaptive and collaborative leadership, quality mentoring systems, and a digital-based spiritual reinforcement approach. This study contributes to the development of a VUCA-based educational quality framework that is adaptive and sustainable in Islamic education contexts.